Abortion access in the Americas: a hemispheric and historical approach - Roth, Cassia (Frontiers in Public Health, 2023)
This perspective article situates the 2022 United States (U.S.) Supreme Court's overturning of Roe v. Wade (1973) within the broader history of abortion rights activism and legislation in the greater Americas. The U.S. public has stereotyped Latin America and the Caribbean (LAC) as socially conservative regarding gender issues and anti-reproductive rights. But twenty-first-century LAC presents a more complicated landscape than this dominant narrative suggests. In the past fifteen years, political, legislative, and public health advances and setbacks across the region provide both a blueprint for re-establishing access to safe and legal abortion and a warning on the consequences of the criminalization of abortion for the United States.